2016
DOI: 10.1080/10790268.2016.1151145
|View full text |Cite
|
Sign up to set email alerts
|

Changes in pain and quality of life in depressed individuals with spinal cord injury: does type of pain matter?

Abstract: Objective: To examine the association of neuropathic and nociceptive pain severity and interference with quality of life (QoL) in persons with spinal cord injury (SCI) who underwent a randomized controlled 12-week trial of an antidepressant to treat depression. A secondary objective was to assess the effect of changes in pain on mobility and physical independence. Design: Multivariable ANCOVA models controlling for relevant demographic covariates, treatment condition, and baseline pain and QoL were used. Setti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 46 publications
0
7
0
3
Order By: Relevance
“…A second study found that those with NP had significantly lower QoL compared to those reporting no pain or nociceptive pain (Andresen et al., ). A third study found no extensive relationship between pain phenotype and QoL although the study population comprised patients with a major depressive disorder, limiting interpretation of the results (Richardson et al., ). Limitations in studies to date include failure to employ a detailed QoL measure and that data were not drawn from in a national population sample.…”
Section: Introductionmentioning
confidence: 99%
“…A second study found that those with NP had significantly lower QoL compared to those reporting no pain or nociceptive pain (Andresen et al., ). A third study found no extensive relationship between pain phenotype and QoL although the study population comprised patients with a major depressive disorder, limiting interpretation of the results (Richardson et al., ). Limitations in studies to date include failure to employ a detailed QoL measure and that data were not drawn from in a national population sample.…”
Section: Introductionmentioning
confidence: 99%
“…De acordo com Mota; Ribeiro (2016), em estudo transversal composto de 118 pacientes com idade média de 34,7 anos, observou-se alta prevalência de lesão por pressão em pessoas com TRM, sendo a avaliação da qualidade de vida elucidada por uma insatisfação significativa referente aos aspectos físicos. Outro estudo com abordagem metodológica semelhante, identificou a dor como um fator que diminui a QV dos pacientes estudados 11 .…”
Section: Descrição Dos Estudosunclassified
“…The presence of pain, and in particular, the location of the pain, is associated with functional independence. For instance, if individuals with SCI have pain in the upper extremities, it may impact their ability to use a wheelchair and perform basic activities of daily living (24). Taken together, some sociodemographic and injuryrelated variables are likely to contribute to QOL in PwSCI; however, other psychological factors also affect adaptation outcomes.…”
Section: Introductionmentioning
confidence: 99%